2005
DOI: 10.1111/j.1365-313x.2005.02535.x
|View full text |Cite
|
Sign up to set email alerts
|

Oleate desaturase enzymes of soybean: evidence of regulation through differential stability and phosphorylation

Abstract: The endoplasmic reticulum-associated oleate desaturase FAD2 (1-acyl-2-oleoyl-sn-glycero-3-phosphocholine Delta12-desaturase) is the key enzyme responsible for the production of linoleic acid in non-photosynthetic tissues of plants. Little is known, however, concerning the post-transcriptional mechanisms that regulate the activity of this important enzyme. The soybean genome possesses two seed-specific isoforms of FAD2, designated FAD2-1A and FAD2-1B, which differ at only 24 amino acid residues. Expression stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
176
2
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(191 citation statements)
references
References 49 publications
(48 reference statements)
5
176
2
4
Order By: Relevance
“…Turnover-Previous analyses implicated the ERAD pathway in the degradation of mammalian SCD (71), plant Fad2 (15), and yeast SCD (29), and here we have demonstrated that Fad3 proteins are also degraded by a UPS-dependent process in both yeast (Fig. 7) and plant (Fig.…”
Section: Identification Of Specific Components Of the Erad Pathway Inmentioning
confidence: 80%
See 2 more Smart Citations
“…Turnover-Previous analyses implicated the ERAD pathway in the degradation of mammalian SCD (71), plant Fad2 (15), and yeast SCD (29), and here we have demonstrated that Fad3 proteins are also degraded by a UPS-dependent process in both yeast (Fig. 7) and plant (Fig.…”
Section: Identification Of Specific Components Of the Erad Pathway Inmentioning
confidence: 80%
“…3C), lysine residues were shown to be important for determining SCD half-life, with substitution of a single lysine residue within an N-terminal sequence resulting in a significant increase in protein half-life (70). The ER-localized Fad2 enzymes of plants have been also shown to contain degradation signals within their N termini (15). Unlike Fad3, however, the plastidial Fad8 enzyme has been shown to contain a distinct degradation signal within the last 44 amino acids of the protein sequence (16), with the difference in positioning of these degradation signals in Fad8 and Fad3 possibly being a reflection of unique aspects of their protein biogenesis.…”
Section: Identification Of An N-terminal Degradation Signal In Fad3mentioning
confidence: 99%
See 1 more Smart Citation
“…In wheat, FAD2 was induced at low temperature and also correlated with the enhanced eukaryotic pathway. In developing seeds, an induction of FAD2-1 and FAD2-2 expression in soybean (Glycine max) at high temperature has been reported previously (Heppard et al, 1996), but that was rationalized in the context of posttranscriptional regulation of enhanced degradation of the soybean FAD2-1 (Tang et al, 2005). However, it is also possible that the induction of FAD2 was associated with a higher lipid pathway activity through the eukaryotic pathway in developing seeds.…”
Section: Key Factors Influencing Glycerolipid Pathway Adjustment Undementioning
confidence: 85%
“…The ER-localized FAD3 is regulated extensively by both temperature-dependent changes in translational efficiency and modulation of protein half-life (27,28). Furthermore, expression of FAD2 in yeast cells reveals a short half-life, and its abundance is also modulated by temperature, although the details of the turnover mechanism are currently unknown (29,30).…”
Section: Resultsmentioning
confidence: 99%